2009
DOI: 10.1186/1471-5945-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of aquagenic pruritus in a young African population

Abstract: Background: Aquagenic pruritus (AP) occurs during or after contact of the skin with water such as occurs in bathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
1
20
2
2
Order By: Relevance
“…The exact prevalence of aquagenic pruritus is not exactly known and some of the facts/figures obtained about prevalence are environment-based [4]. Salami et al, conducted a study at south western Nigeria and they reported a prevalence of 23.5 % [4]. Again Olumide and Oresanya confirmed a prevalence of 21% in another study done at Lagos, Nigeria [5].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The exact prevalence of aquagenic pruritus is not exactly known and some of the facts/figures obtained about prevalence are environment-based [4]. Salami et al, conducted a study at south western Nigeria and they reported a prevalence of 23.5 % [4]. Again Olumide and Oresanya confirmed a prevalence of 21% in another study done at Lagos, Nigeria [5].…”
Section: Introductionmentioning
confidence: 74%
“…Some physicians have attributed this to a psychiatric-like problem [5]. The exact prevalence of aquagenic pruritus is not exactly known and some of the facts/figures obtained about prevalence are environment-based [4]. Salami et al, conducted a study at south western Nigeria and they reported a prevalence of 23.5 % [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der durch Wasser ausgelöste brennende Schmerz wird auch als Aquadynie bezeichnet und als Variante des AP angesehen . Die Prävalenz des AP variiert von 1,4–23,8 % .…”
Section: Aquagener Pruritusunclassified
“…However, certain dermatological entities accompanied by itch are more prevalent in non‐Caucasian populations 1 . The prevalence of aquagenic pruritus was found to be 23.8% in Nigeria, which is five times higher than that in Israel 4 . Chloroquine‐induced pruritus is less prevalent in Asians and Caucasians than it is in Africans 5,6 .…”
Section: Introductionmentioning
confidence: 99%